The portrayal of the Bulgarian Tsar Samuel in the Byzantine sources (10th–12th c.) (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
Information included in the Byzantine sources (e.g.: John Skylitzes, Nicephor Bryennios, Anna Komnene, John Zonaras, Michael Glykas, The Life of Nikon Metanoeite), analysed in the present article and relating to Samuel are focused on the two fundamental questions, specifically the circumstances in which he had taken the reins of power and the military activity he conducted against Byzantium.